2006
DOI: 10.5367/000000006777637449
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Contribution of a Multi-Purpose Event Facility to the Area Economy

Abstract: While the economic impacts of professional sports events and entertainment facilities in major metropolitan areas have been the subject of numerous studies, sports and entertainment facilities in smaller cities have received less attention. This study addresses the economic impact of a multi-purpose sports and auditorium facility located in a small metropolitan area. Intercept surveys at eleven representative events provided information on attendees' expenditures and residence and on the role of the event in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…For example, perhaps estimating the impact of all the events hosted in one community or at a specific event venue may be the objective. An examination of the research question may lead to the hypothesis that the events may differ substantially with regard to attendee attributes (e.g., residence, income) and expenditures (Hodur et al, 2006). In such cases, it is important to select a representative sample of events.…”
Section: Sampling and Event Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, perhaps estimating the impact of all the events hosted in one community or at a specific event venue may be the objective. An examination of the research question may lead to the hypothesis that the events may differ substantially with regard to attendee attributes (e.g., residence, income) and expenditures (Hodur et al, 2006). In such cases, it is important to select a representative sample of events.…”
Section: Sampling and Event Selectionmentioning
confidence: 99%
“…Study results indicated that attendee attributes and expenditures did indeed differ substantially by event type. For example, expenditures (in addition to tickets and other spending within the facility) per non-local attendee ranged from $310 for a multi-day amateur athletic competition to $105 for a college football game to $26 for a high school sports event (Hodur et al, 2006).…”
Section: Sampling and Event Selectionmentioning
confidence: 99%
See 3 more Smart Citations